The Prosody of the Czech Discourse Marker 'Jasně': An Analysis of Forms and Functions - Volin, Jan; Weingartová, Lenka; Niebuhr, Oliver (Phonetica, 2016)
Words like yeah, okay and (al)right are fairly unspecific in their lexical semantics, and not least for this reason there is a general tendency for them to occur with highly varied and expressive prosodic patterns across languages. Here we examine in depth the prosodic forms that express eight pragmatic functions of the Czech discourse marker jasně, including resignation, reassurance, surprise, indifference or impatience. Using a collection of 172 tokens from a corpus of scripted dialogues by 30 native speakers, we performed acoustic analyses, applied classification algorithms and solicited judgments from native listeners in a perceptual experiment. There appeared to be multi-parametric differences between jasně realizations in terms of their F0, timing and intensity patterns, which gave rise to generally consistent form-function mappings. For example, resignation seems to be realized with a falling intonation contour, relatively slow tempo, long wordinitial consonant and a short word-final vowel. Although the most significant prosodic parameters used for clustering analysis involved segment durations, all pragmatic functions were expressed by patterns of multiple features.
Keywords: jazyk (prostředek komunikace); Verbal Behavior; komunikace; akustika řeči; Česká republika; Semantics; mužské pohlaví; Speech Acoustics; Czech Republic; ženské pohlaví; sémantika; Humans; Communication; Speech Perception; Language; percepce řeči; verbální chování; Phonation; fonace; Female; lidé; Male